2019
DOI: 10.1111/1440-1630.12563
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of simulated and traditional clinical placements in occupational therapy education

Abstract: Introduction: This economic evaluation complements results of the randomised controlled trial that established non-inferiority of the learning outcomes of a one-week simulated clinical placement (SCP) in occupational therapy qualifying degrees in comparison to an equivalent traditional clinical placement (TCP). This companion study presents detailed cost analyses of two placement alternatives and a cost-benefit study to assess the value for money of SCP. An economic evaluation of simulated versus traditional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…A second significant set of limitations relates to how outcomes or effects are considered, specifically the heterogeneity of outcomes examined, the lack of use of validated measures, and limited selection of points at which effects were assessed. With the exception of the RCT by Imms et al (2018) and its associated economic evaluation (Gospodarevskaya et al, 2019), measurement in quantitative studies focused on narrow outcomes. For instance, the RCT by Sevenhuysen et al (2014) evaluated the time released for non-student activities and the volume of feedback provided to students, while Zeira and Schiff (2010) and Cleak and Smith (2012) used survey methods to assess satisfaction with the models used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A second significant set of limitations relates to how outcomes or effects are considered, specifically the heterogeneity of outcomes examined, the lack of use of validated measures, and limited selection of points at which effects were assessed. With the exception of the RCT by Imms et al (2018) and its associated economic evaluation (Gospodarevskaya et al, 2019), measurement in quantitative studies focused on narrow outcomes. For instance, the RCT by Sevenhuysen et al (2014) evaluated the time released for non-student activities and the volume of feedback provided to students, while Zeira and Schiff (2010) and Cleak and Smith (2012) used survey methods to assess satisfaction with the models used.…”
Section: Discussionmentioning
confidence: 99%
“…While the study by Sevenhuysen et al (2014) found no difference in educator workloads or service provision, its sample size (n ¼ 24) may not have been sufficient to detect changes. Conversely, the RCT by Imms et al (2018) was adequately powered, but the associated economic evaluation (Gospodarevskaya et al, 2019) did not examine changes in service productivity associated with the presence or absence of students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the institute is fighting for accountability, accreditation, and implementation of the mission to achieve success, productivity, and satisfaction, much resources and time should be directed toward faculty development (15). The importance of faculty development was stressed by Harden (2009) as being equivalent to curriculum development, which is a very difficult assignment [16,17]…”
Section: Introductionmentioning
confidence: 99%